HUBUNGAN ANTARA DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN TINGKAT STRES PADA MAHASISWA YANG SEDANG MENGERJAKAN SKRIPSI DI STIKES PIALA SAKTI PARIAMAN - KASMORA, DEPERMAN; ARINI, LARASUCI; TANJUNG, ULIL AMRI; PARDAMEAN, BISMAR (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2024)
Thesis assignment is a difficult final assignment and takes a long time so that it has an impact on psychology and physical so that it gives rise to negative attitudes in making the title or the process of working on it. Difficulties in doing thesis assignments faced by a nursing student can trigger stress. The purpose of this study was to determine the relationship between peer social support and stress levels in students working on their thesis at STIKES Piala Sakti Pariaman. This type of quantitative research with a descriptive analytical design with a Cross Sectional Study approach. The research sample consisted of 36 people. Sampling was done by total sampling. Statistical tests using Chi Square. The results of the study showed that most (61.1%) respondents received social support from peers in compiling their thesis. Most (72.2%) respondents experienced mild stress in compiling their thesis. The results of the square test statistical test obtained a value of P = 0.005 (P <0.05). In conclusion, there is a significant relationship between peer social support and stress levels in students working on their thesis at STIKES Piala Sakti Pariaman.